Growth‐competition‐herbivore resistance trade‐offs and the responses of alpine plant communities to climate change. (12th March 2018) - Pellissier, Loïc; Descombes, Patrice; Hagen, Oskar; Chalmandrier, Loïc; Glauser, Gaétan; Kergunteuil, Alan; Defossez, Emmanuel; Rasmann, Sergio
Abstract: Climate change is expected to modify current ecological conditions sustaining the coexistence of species within cold‐adapted plant communities. It will primarily act upon the existing structure of communities, whose response should depend on the functional differences governing coexistence among alpine species. We postulated that a possible trade‐off between (1) plant growth in response to temperature, (2) plant competition and (3) resistance to herbivory, modulates the rate of plant community turnover under climate change. We reviewed the literature investigating functional traits variability within communities along elevation gradients. Despite environmental filtering, our review indicates that interspecific plant functional variation within communities does not necessarily decrease with elevation. While the diversity of traits related to abiotic affinities or competition are well documented, the variability in species resistance to herbivory within communities is poorly known. Using a Lotka–Volterra‐based model, we simulated the impact of climate change on plant communities through (1) a direct effect on plant growth and competition and (2) an indirect effect via an increase in herbivore pressure. We showed that different shapes of trade‐offs between temperature‐related growth, competition and resistance to herbivory modulate community turnover under climate change. We documented the existence of two independent trade‐offs axes using a detailed dataset of functional traits within two alpine grasslands in the European Alps. Plant competitive traits (i.e. leaf area and height) where negatively associated to cold tolerance, whereas traits of the leaf economic spectrum were associated to traits related to the physical resistance to herbivory. We propose that the immediate effect of climate change on alpine plant communities will depend on existing functional variability and how functional axes trade‐off with each other. Documenting ecological constraints between plant functional axes should provide indications to anticipate winners and losers in alpine plant communities. A plain language summary is available for this article. Abstract : Plain Language Summary